RESTORATIVE JUSTICE IN INDONESIA: TRADITIONAL VALUE - Zulfa, Eva Achjani (Indonesia Law Review, 2011)
“Restorative Justice” is a model approach which emerged in the 1960s in an effort to solve criminal cases. Unlike the approach used in conventional criminal justice system, this approach focuses on the direct participation of perpetrators, victims and society in the settlement process. This theory of the approach is still debated, but the view is in fact growing and it exercises a lot of influence on legal policies and practices in several countries. The UN through its basic principles considers the approach of restorative justice as the approach which could be used in the rational criminal justice system. Restorative justice is a concept of thinking that supports the development of the criminal justice system with emphasis on the required involvement of the community. It is also involving the casualties who with the current criminal justice system are excluded. In several countries, restorative justice has been translated into a variety of formulations to accommodate a variety of values, philosophical basis, terms, strategies, mechanisms, and programs. Good consultation with the perpetrators and the victims themselves may provide the public with a different mindset in preventing emerging problems. This process can involve the police, prosecutorial institution or the traditional institutions. Therefore, without excluding the work in the formal legal system, the institutional mechanism for resolution through consultation was working in the community. In the various principles and models of the restorative justice approach, the process of dialogue between the perpetrator and the victim is a fundamental and the also the most important part of the application of the restorative justice. The direct dialogue between the perpetrator and the victim gave the victim the opportunity to express what he/she felt, hope for human rights and the desire to reach a criminal settlement.